The Analyst of Interactive Lecturing Approach to Enhance the Students’ Learning Motivation in Higher Education Institutions - Ningsih, Wirda (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2024)
Lectures can range from being fully focused on the teacher to valuing learner-teacher and learner-learner interaction. Advocates of the completely didactic (teacher-cantered) lecture want to maximize the amount of lecture time available for material delivery, viewing other activities as 'lost' lecture time. However, educational research has found the potential benefit of interactivity in promoting cognitively active learning and better learning outcomes. This study aim is to find out the interactive lecture approach to drive of students learning motivation in higher education. The research was the qualitative research approach. The data was found from library research. The results are the strategies for interactive lecturing consist of encourage active participation, utilize multimedia and advanced technology Encourage teamwork and peer learning, give practical illustrations and applications, provide formative evaluations, develop a conducive learning environment, individualize educational experiences, Provide clear objectives and outcomes in learning process.